TINJAUAN YURIDIS PELAKSANAAN PUTUSAN PENGADILAN TATA USAHA NEGARA PASCA PERUBAHAN UNDANG-UNDANG NOMOR 5 TAHUN 1986 - Hariyono, Agus; Dharma Kusuma, A. A. Gde Agung (Kertha Negara : Journal Ilmu Hukum, 2014)
Based on scientific papers entitled "judicial review implementation of the Administrative court ruling after a change in law number 5 of year 1986”, the author uses a normative research method. Law number 5 of year 1986 concerning administrative courts is a procedural law in the administrative courts. The Law was changed by new law number 9 year of 2009 and law number 51 year of 2009. With the change of Amendment Act than raised the several issues. Firstly, how to implement the decision of the State Administrative Court after the change. The secondly is the constraint in the implementation of the court decision forced effort. Relating to the conduct of the court system, these changes alter the enforcement of a system of self-respect that is where the execution of court decisions left entirely to the consciousness of the body or the State administration officials into execution the fixed system where the court can impose administrative implementation of the court decision forced the country through the efforts of governed by legislation. Related Constraints faced in implementation efforts in the implementation of court decisions forced clerical State is the lack of further regulation relating to the technical implementation of forceful measures.
Keywords: Proceeding Law, Administrative court, forceful measures